Socioeconomic and political determinants of five common cancers in the MENA region - Ali Reza Hadi Poor; Parisa Mehdizadeh; Sayyed Morteza Hosseini Shokouh; Mohammad Meskarpour Amiri (Acta Psychologica)
Cancer is a leading cause of incidence and death globally, and the MENA region, with its diverse socioeconomic and political landscape, exhibits significant disparities in cancer incidence and mortality rate. This study aims to investigate the influence of socioeconomic and political factors on the incidence and mortality rate of the five most common cancers—lung, breast, colorectal, stomach, and prostate—in the MENA region over the past two decades. We conducted a panel data analysis of 23 MENA countries from 2001 to 2020, utilizing data on cancer incidence and mortality from the Institute of Health Metrics and Evaluation (IHME) and socioeconomic and political indicators from the World Bank and United Nations databases. The fixed effects (FE) model was employed to estimate the impact of GDP per capita, mean years of schooling, unemployment rate, and governance quality index on cancer outcomes. Health risk exposure and total health expenditure were included as control variables. The FE model results indicated that higher GDP per capita and improved governance quality were positively associated with cancer incidence but significantly reduced mortality rates, particularly for lung, prostate, and breast cancers. Education and employment also contributed to lower mortality rates, while exposure to health risk factors increased both incidence and mortality. Therefore, improving socioeconomic and political conditions, particularly through sustainable economic growth, enhanced governance, and better education, is crucial for reducing cancer mortality in the MENA region. Policymakers should prioritize these areas to effectively combat the cancer burden and improve public health outcomes.